Дослідження в Дубно по вул. Замкова, 10 - Прищепа, Б.А.; Чекурков, В.С.; Ткач, В.В. (Археологічні дослідження в Україні, 2010)
Results of the works in Dubno at 10, Zamkova Street in 2009 are presented. At the area allotted for construction, the layers and objects of Slavonic and Rus period and Lithuanian-Polish epoch were discovered that provided the evidence of the continuous development of the settlement since the 10th c. to the middle of the 13th c.